Decomposing inequality changes in Uruguay: the role of formalization in the labor market - Verónica Amarante; Rodrigo Arim; Mijail Yapor (IZA Journal of Labor & Development, 2016)
During the first decade of the twentieth century, the Uruguayan labor market showed a significant decline in wage inequality and in the incidence of labor informality, while similar changes also took place in other Latin American countries. These trends were observed in a period of strong economic dynamism. Most extended explanations for this declining inequality in the region have been centered on falling returns to education. The main goal of this paper is to present new evidence on the relation between informality and wage inequality through a RIF-based regression decomposition analysis which, besides confirming the relevant role of education, shows that the process of labor market formalization also played a significant role in the reduction of inequality in Uruguay, mainly through a price effect.
Keywords: D31; J31; 330; Inequality; Informality; Microeconometric decompositions